Kajian Multi Varian Faktor yang Berpengaruh terhadap Infiltrasi Air Tanah sebagai Dasar Penentuan Daerah Potensial Resapan Air Tanah - Daniel Eko Aryanto; Gagoek Hardiman (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2017)
Ground water is one of the most valuable and influential natural resources affecting human life. The groundwater recharge area is very important because its function is to maintain the balance and sustainability of groundwater. One of the most effective and efficient methods for determining the groundwater recharge potential area is with the geographic information system. The approach with geographic information system is done by overlapping thematic maps on the factors that affect to groundwater infiltration. Overlapping thematic maps on weighting and scoring their effects on groundwater recharge potential areas. This study aims to determine the factors that affect and the weight of its effect on the groundwater recharge with the study of the literature as a conservation material to support the sustainability of the groundwater. The data used is secondary data from literature review.